Damage and stress evolution in the bondlines of metallic adhesively bonded joints accompanied by bondline thickness effect. (June 2015) - Xu, Wei; Yu, Huichen; Tao, Chunhu
Abstract: Metallic adhesively bonded joints have a wide range of applications in engineering fields. The damage and the stress evolution in the bondlines of the joints would occur simultaneously when the joints are subjected to external loads. In the present research, the influence of the bondline thickness on the damage and stress evolution of metallic adhesive bonding structures are investigated, with the cohesive interface model employed to equivalently simulate the bondline with various thicknesses. A prediction approach is employed to determine the cohesive parameters for the bondline with the thickness varied. Then a numerical example is presented to explore the bondline thickness-dependence strength and stress distribution in the bondline, followed by the validation with the existing experimental and theoretical results. Furthermore, as the main part of this paper, the influences of the bondline thickness on the damage and stress evolution in the bondline are investigated, involving the situations of the extremities and the whole bondline. The results show that, no matter in the extremities or in the whole bondline, the damage and stress evolutions are mutually influential processes, both of which are affected by the bondline thickness significantly.